EVALUASI KINERJA SEISMIK JEMBATAN EXISTING BETON PRATEGANG VOIDED SLAB DENGAN ANALISIS PUSHOVER PADA PILAR JEMBATAN - Ahmad Afifi (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
The standard code of planning and loading bridges in Indonesia has undergone several changes, especially in the earthquake load planning aspect, with the latest changes in 2016, namely SNI 2833:2016 and SNI 1725:2016. With this change in standard codes, bridges that were already operating in Indonesia before 2016 needed to be evaluated on their structural performance. In this paper, evaluation was conducted on a pre-stressed bridge with voided slab type, such as Bridge 5 Cawang Interchange at Jakarta Intra Urban Tollway which has been built since 1987. The evaluation results howed that the axial-bending capacity of the bridge pier elements was not able to carry loads with the latest standard codes in extreme boundary conditions. In addition, the required area of confinement reinforcement on the bridge pier elements does not meet the minimum requirements. Furthermore, evaluation of bridge structure performance is carried out by using static pushover analysis (NSPA) on the pier P3 element bridge loading toward longitudinal direction, resulting P3 performance in Operational - Life Safety (O-LS) conditions reach a drift of 1.56%. Ultimately, when the structural retrofitting model is applied to the P3 pier element with RC-jacketing fc' 25 MPa with a thickness of 100 mm and additional longitudinal reinforcement of 72 D29, the P3 capacity is expected to increase by 49% from the initial capacity and the performance level will decrease to the Operational level (O) with a drift of 1%